Investigation of the Effects of Distributed Generation on Protection Coordination in a Power System - Tariq, A.; Khatri, K. L.; Haque, M. I. U.; Raza, M. A.; Ahmed, S.; Muzammil, M. (Engineering, Technology & Applied Science Research, 2021)
The rapid increase of the electrical power demand gave rise to many challenging situations for power system control engineers as the transmission lines are operating at their maximum capacity in most developing economies. To solve this, Distributed Generation (DG), i.e. the generation of electrical power in a distribution network that provides clean energy, is gaining popularity. There are several challenges the protection of distribution networks faces after DG installation, such as variations in short circuit levels, protection blinding, reverse power flow, protection coordination, change in fault impedance, recloser-fuse coordination, selectivity, unsynchronized reclosing, false tripping, etc. In this paper, an IEEE 13-Bus System Radial Distribution System is simulated using Electrical Transient Analyzer Program (ETAP), various scenarios of DG placement are considered, their impact on the protection system is analyzed, and different techniques are proposed to minimize the effect on protection coordination. The use of directional relays, current limiting reactors, and small magnitude DGs is tested and analyzed. The way this effect varies by changing the location of DG is also analyzed.